MPPT implementation and simulation using developed P&O algorithm for photovoltaic system concerning efficiency - Asaad A. H. AlZubaidi; Laith Abdul Khaliq; Hassan Salman Hamad; Waleed Khalid Al-Azzawi; Mohanad Sameer Jabbar; Thaer Abdulwahhab Shihab (Institute of Advanced Engineering and Science, 2022)
The great development witnessed by investments in renewable energy has made it the focus of researchers’ attention in order to increase its efficiency. This is due to the increase in demand for electrical energy due to rapid technological growth, increase in population numbers, and high fuel prices that are used in the production of traditional electrical energy, but it suffers from a problem that is greatly affected by two factors, namely, the change in the intensity of solar irradiation and temperature, which makes its electrical characteristics non-linear, which causes a decrease in its efficiency. To address the efficiency problem, the researchers developed several techniques for tracking the MPP point and extracting the maximum energy from the solar panels under various measurement conditions. Maximum power point tracking technology (MPPT) technology is the most widely used technology in solar energy systems. In this article, MPPT technology is simulated using MATLAB/Simulink for the purposes of extracting maximum power and managing the duty cycle of a DC-DC buck converter. The performance of the photovoltaic system under various irradiance fluctuations and settings of constant temperature could well be determined using simulation results. Under standard and varied test settings, allowing the inverter to convert over 99% of the electricity provided by the solar panels.